Ruthenium-catalyzed hydrogen generation from glycerol and selective synthesis of lactic acid. Issue 1 (13th October 2014) - Li, Yang; Nielsen, Martin; Li, Bin; Dixneuf, Pierre H.; Junge, Henrik; Beller, Matthias
Abstract : Methods for hydrogen generation from glycerol and selective synthesis of lactic acid (67%) as well as other polyols are presented. Abstract : An efficient hydrogen generation from glycerol and selective synthesis of lactic acid (67%) using pincer-type ruthenium complexes is described. Analysis of the products from glycerol dehydrogenation indicates that improving the efficiency of the decarboxylation step is a key point for further reforming processes.